Proteomic analysis of the effect of hemin in breast cancer - Colo, Georgina Pamela (2023)
Heme, an iron-containing prosthetic group found in many proteins, carries out diverse biological functions such as electron transfer, oxygen storage and enzymatic reactions. Hemin, the oxidised form of heme, is used to treat porphyria and also to activate heme-oxygenase (HO) which catalyses the rate-limiting step in heme degradation. Our group has previously demonstrated that hemin displays antitumor activity in breast cancer (BC). The aim of this work has been to study the effect of hemin on protein expression modifications in a BC cell line to gain insight into the molecular mechanisms of hemin antitumor activity. For this purpose, we carried out proteome analysis by Mass Spectrometry (MS) which showed that 1309 proteins were significantly increased in hemin-treated cells, including HO-1 and the proteases that regulate HO-1 function, and 921 proteins were significantly decreased. Furthermore, the MS-data analysis showed that hemin regulates the expression of heme- and iron-related proteins, adhesion and cytoskeletal proteins, cancer signal transduction proteins and enzymes involved in lipid metabolism. By biochemical and cellular studies, we further corroborated the most relevant in-silico results. Altogether, these results show the multiple physiological effects that hemin treatment displays in BC and demonstrate its potential as anticancer agent.